Transdisciplinary treatment of Class III malocclusion using conventional implant-supported anchorage: 10-year posttreatment follow-up - Mariana Roennau Lemos Rinaldi; Susana Maria Deon Rizzatto; Luciane Macedo de Menezes; Waldemar Daudt Polido; Eduardo Martinelli Santayanna de Lima (Dental Press Editora, 2015)
INTRODUCTION: Combined treatment offers advantages for partially edentulous patients. Conventional implants, used as orthodontic anchorage, enable previous orthodontic movement, which provides appropriate space gain for crown insertion. OBJECTIVE: This case report describes the treatment of a 61-year and 10-month-old patient with negative overjet which made ideal prosthetic rehabilitation impossible, thereby hindering dental and facial esthetics. CASE REPORT: After a diagnostic setup, conventional implants were placed in the upper arch to anchor intrusion and retract anterior teeth. Space gain for lateral incisors was achieved in the lower arch by means of an orthodontic appliance. CONCLUSIONS: Integrated planning combining Orthodontics and Implantology provided successful treatment by means of conventional implant-supported anchorage. The resulting occlusal relationship proved stable after 10 years.